The Effectiveness of Group Guidance to Improve Students’ at Darul Uloom School Satun Thailand - Asnaini Agusnar; M. Fauzi Hasibuan; Sri Ngayomi Yudha Wastuti (Universitas Muhammadiyah Enrekang, 2024)
This research focuses on the role of Educational Guidance and Counseling (EGC) in supporting students' adjustment at Darul Uloom School, Satun, Thailand. Utilizing a qualitative approach through a case study, the study explores the dynamic interaction between students and EGC in the context of multicultural Islamic education. The research findings highlight the challenges students face in adapting to new environments, cultures, and languages. The key role of EGC is identified in assisting students in overcoming these challenges through group counseling. Practical recommendations are provided to strengthen cultural adjustment programs, student-centered learning, and collaboration among schools, parents, and communities to enhance the quality of education in multicultural environments. The implications of this research contribute to the literature on group counseling and Islamic education, offering practical guidance for similar institutions.